Scientific discourse in Education: Rhetorical and structural analysis of research articles from Colombia and Venezuela. - Blanco, Carlos Eduardo (2019)
The scientific discourse of Education is disseminated primarily through written genres and the research article is a fundamental one. This study is based on the theory of the superstructural sections of these discourse genres. Its purpose has been to contribute to a characterization of aspects of academic writing and publication in a very relevant area of knowledge, Education, in two Latin American countries. The objective of the examine, descriptive, exploratory and non-experimental was to analyze structurally and rhetorically a set of 52 research articles of this discipline in refereed journals from Colombiaand Venezuela. The superstructural sections of the articles were analyzed in order to find out how these texts conform to an official or institutional rhetoric of science. Results show that the research articles analyzed tend to adapt to the official rhetoric, albeit only partially. However, texts dealing with historical topics almost always move away from the canonical schematization of such rhetoric. These results could be due to characteristics of the discipline of education, humanistic and interdisciplinary in nature, to historical and philosophical traditions, as well as to the context of the production of texts, that is, the Latin American critical university, with its particular problems.